Financial feasibility of marine tourism hospitality sector post-pandemic outbreak of Covid-19: case study from small islands regions - Ngangun, Tati Atia; Pentury, Frischilla (Fakultas Ekonomi dan Bisnis, Telkom University., 2023)
The challenge faced by small and micro enterprises in remote islands is the ability to maintain the consistency of the production and revenue. The marine tourism sector in Kei Islands, like many sectors dealt and is still facing the same roadblock to visitor growth and consistency after the COVID-19pandemic hit and is still recovering. Thus, it is important for the local hospitality sector to measure the projectionof their business. The purpose of the study was to identify the financial feasibility of the hospitality sector in the Kei Islands region. By doing so, two beach resorts and two restaurants were selected as the study cases located in the famous and famous marine tourism spot in the region, which is Ngurbloat Beach. The field survey was conducted in August 2022 by in-depth interviews and questionnaires to collect the field data from owners of resorts and restaurants. The indicators of financing feasibility that were used in this study were B/C, profit, R/C, NPV, IRR, and yearly profitability projection. The result showed that for each beach resort and restaurant, all the criteria showed that those were still feasible for the next five years. Although the results also indicated that for the current stance, the profitability projection for the next five years had a downward trend compared to the present year. Therefore, promotion and the effectiveness of government handling post-pandemic are important insignificantly increasing the profitability of the hospitality sector in the region. Keywords— Hospitality; Financial Feasibility; Marine Tourism; Profitability